THE EFFECT OF EXPOSITORY METHODON READING NARRATIVE TEXT ABILITY AT THE GRADE VIII OF SMP NEGERI 1 ANGKOLA TIMUR - Abdul Rahman Siagian (Universitas Muhammadiyah Tapanuli Selatan, 2017)
This research conducted to find out whether there was effect of expository method to reading narrative text at the grade VIII of SMP Negeri 1 Angkola Timur. To conduct this research, experimental research method had been applied by the writer,then the writer took sample by using cluster sampling and To collect the data, the writer used observation and test. Observation used to get data of the using expository method. Test used to get data of reading narrative text ability. To analyzed the data, the writer used descriptive and statistic by using t-Test formulation. Based on the descriptive analysis, it could be seen that the students good category before using expository method in reading narrative text ability of the score 69.8. In other side, it could be seen that the students at the grade VIII of SMP Negeri 1 Angkola Timur got very good category after using expository method in reading narrative text ability to got the score 80.6. Thus, it could be said that expository method tended to one factor that affected the students’ reading narrative text at the grade VIII of SMP Negeri 1 Angkola Timur.